A Globo Shippa Muito Clanessa: a configuração do fandom Clanessa na dinâmica transmídia do BBB14 - Arthur Guedes Mesquita (2016)
The reality show Big Brother Brasil has a multiplatform transmission in which it is evident a transmedia dynamic constituted in the relation between multiple media that implies an engaged and participative audience. In the 14th edition of the show, the emergence of the Clanessa fandom, conformed from the relationship between the participants Clara and Vanessa, was able to not only influence the direction of the reality but to present a community with its own characteristics. The clanessas as they became known started to watch BBB14 (2014) from the perspective of the relation between Clara and Vanessa, creating parallel stories and organizing ways that both participants continued in the show till the end. The emergence of the fandom showed itself as a rich phenomenon to comprehend the dynamics of its formation and the agency of the fans towards the visibility of subjects connected to their lesbian identities. As they articulated themselves in social media sites specially, on Twitter , the clanessas caused a transmedia arrangement that was leveraged by the television transmission while questioned and tensioned the narratives constructed by Rede Globo. Therefore, we seek to understand which topics emerged as constituted and constitutor of the Clanessa fandom in the BBB scenario. After collecting tweets from January 7th of 2014 (date that Rede Globo released the participants of the 14th edition) till April 9th of 2014 (date that the show Encontro com Fátima Bernardes dedicated to the fandom was aired), we identified the tension of two main issues: the fight towards visibility so they could be acknowledged as a community and the political dimension attached to the social power of therelationship of Clara and Vanessa that extrapolate the affection between the two of them.